STRATEGI PEMBELAJARAN DIFERENSIASI DALAM PEMBELAJARAN AKIDAH AKHLAK UNTUK MEMENUHI KEBUTUHAN HETEROGENITAS SISWA MTS MA’ARIF GONDANG - Afifah Afni Novalia; Diya Nur Ramadhani; Misbahudin Misbahudin; Ahmad Zaffi Syafiq; Robingun Suyud El Syam (JURNAL ILMIAH NUSANTARA, 2026)
Learning in the subject of Akidah Akhlak is inherently faced with heterogeneous student characteristics, including differences in academic ability, learning styles, interests, family background, and readiness to comprehend religious concepts. These variations require teachers to implement instructional strategies that can accommodate diverse learning needs so that every student experiences meaningful and effective learning. Differentiated instruction serves as an approach that provides varied learning opportunities through the adaptation of content, process, and product based on individual student needs. In the context of Akidah Akhlak learning, differentiation enables teachers to adjust the delivery of faith and moral values in ways that are relevant and accessible for students with diverse abilities. This approach not only promotes inclusivity but also enhances student engagement, comprehension of religious principles, and internalization of moral character. This article aims to describe the urgency, implementation practices, and benefits of differentiated instruction in Akidah Akhlak learning as an effort to meet the heterogeneity of students in madrasah settings.